Activation of voltage-gated sodium channels by BmK NT1 augments NMDA receptor function through Src family kinase signaling pathway in primary cerebellar granule cell cultures. (1st December 2020) - Zou, Xiaohan; He, Yuwei; Shen, Liping; Xi, Chuchu; He, Jing; Zhang, Fan; Zhao, Fang; Cao, Zhengyu
Abstract: Voltage-gated sodium channels (VGSCs) are responsible for the generation and propagation of action potentials in excitable cells and are the molecular targets of an array of neurotoxins. BmK NT1, an α-scorpion toxin obtained from the scorpion Buthus martensii Karsch (BmK), produces neurotoxicity that is associated with extracellular Ca 2+ influx through Na + -Ca 2+ exchangers, N -methyl-d -aspartic acid (NMDA) receptors, and L-type Ca 2+ channels in cultured cerebellar granule cells (CGCs). In the present study, we demonstrated that BmK NT1 triggered concentration-dependent release of excitatory neurotransmitters, glutamate and aspartate; both effects were eliminated by VGSC blocker, tetrodotoxin. More importantly, we demonstrated that a threshold concentration of BmK NT1 that produced marginal Ca 2+ influx and neuronal death augmented glutamate-induced Ca 2+ elevation and neuronal death in CGCs. BmK NT1-augmented glutamate-induced Ca 2+ influx and neuronal death were suppressed by tetrodotoxin and MK-801 suggesting that the augmentation was through activation of VGSCs and NMDA receptors. Consistently, BmK NT1 also enhanced NMDA-induced Ca 2+ influx. Further mechanistic investigations demonstrated that BmK NT1 increased the expression level of NMDA receptors on the plasma membrane and increased the phosphorylation level of NR2B at Tyr1472. Src family kinase inhibitor, 1- tert -butyl-3-(4-chlorophenyl)pyrazolo[3, 4- d ]pyrimidin-4-yl]amine (PP2), but not the inactive analogue, 4-amino-1-phenylpyrazolo[3, 4- d ]pyrimidine (PP3), eliminated BmK NT1-triggered NR2B phosphorylation, NMDA receptor trafficking, as well as BmK NT1-augmented NMDA Ca 2+ response and neuronal death. Considered together, these data demonstrated that both presynaptic (excitatory amino acid release) and postsynaptic mechanisms (augmentation of NMDA receptor function) are critical for VGSC activation-induced neurotoxicity in primary CGC cultures. Graphical abstract: Mechanism of BmK NT1-induced neurotoxicity in primary CGC cultures. Activation of VGSCs stimulated by BmK NT1 triggers Na + influx leading to membrane depolarization that induces EAA release in presynaptic vesicle. In the postsynaptic membrane, activation of VGSC stimulates Na + influx that triggers the phosphorylates NR2B receptors in a Src family kinase-dependent pathway. Phosphorylated NR2B receptors translocate to the plasma membrane augmenting the Glu response with subsequent neuronal death. EAA: excitatory amino acid; NR1: NMDA receptor subunit GluN1; NR2B: NMDA receptor subunit GluN2B; SFK: Src family kinase; VGSC: voltage-gated sodium channel; Y1472: Tyr1472. Image 1 Highlights: BmK NT1 stimulates glutamate and aspartate release in cerebellar granule cells. BmK NT1 augments glutamate/N-methyl-d -aspartate (NMDA)-induced Ca 2+ response. BmK NT1 increases NMDA receptor expression in plasma membrane. BmK NT1-augmented NMDA receptor function is Src family kinase-dependent. BmK NT1 induced neurotoxicity involves both pre- and post-synaptic mechanisms.